The Influence of Budget Goal Clarity and Organizational Commitment on Budget Performance: Evidence from Kupang Regency, Indonesia - ., Munawar; Riyadi, Slamet; ., Sumiati (Journal of Ecohumanism, 2024)
The purpose of this research is to examine the impact of budget clear clarity and organizational commitment on budget performance in Kupang Regency, Indonesia. Data from 80 people participating in local government budget management were collected and analyzed using structural equation modeling (SEM). The data show that budget goal clarity has no meaningful effect on budget performance, however organizational commitment has a statistically significant impact. These findings highlight the importance of organizational commitment in improving budget outcomes, implying that local governments should prioritize employee engagement through effective techniques and organizational assistance. In contrast, the negligible influence of budget goal clarity emphasizes the need for more research into the mechanisms by which clear budget goals can contribute to performance. This study adds to our understanding of budget performance drivers and offers practical recommendations for improving financial management procedures in local government. Future research should look into other aspects including leadership styles, communication effectiveness, and staff involvement as potential mediators or moderators in the relationship between budget objective clarity and performance.